Comparative Anatomical and Histological Study of the Stomach in Two Iraqi Birds (Columba palumbus and Tyto alba) - Al-Juboory, Rasha W.; Dauod, Hussain A.M.; Al-arajy, Ali S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study aimed to investigate the anatomical and histological, aspects of the stomach in two different Iraqi birds, (common wood pigeon, Columba palumbus (herbivorous) and the barn owl, Tyto alba (carnivorous). Stomach in the two studied birds IS divided into two parts, glandular or true stomach (proventriculus) and the muscular stomach or gizzard (ventriculus). Proventriculus in the common wood pigeon appeared as fusiform shaped tube and separated from the gizzard by isthmus while in the barn owl, it was pearsshaped , wider and shorter than that of the common wood pigeon and not separated from the gizzard by isthmus. In common wood pigeon, gizzard appeared as biconvex lens lining with yellowish green tissue, the koilin , while in the barn owl, gizzard was pear shape and the koilin was very thin. Mucosa of proventriculus in the two studied birds was rich with simple tubuler glands, the superficial gastric glands which were longer and wider in the barn owl than of those in common wood pigeon and the sub mucosa was rich with compound branched alveolar glands, the deep gastric glands which were longer and wider in the barn owl than those of common wood pigeon. Muscularis externa and serosa in the common wood pigeon were thicker than in the barn owl. Mucosa in the gizzard of the barn owl filled with more gastric pits than the common wood pigeon and the koilin in common wood pigeon was thicker.